Modeling Alzheimer’s disease related phenotypes in the Ts65Dn mouse: impact of age on Aβ, Tau, pTau, NfL, and behavior - Overk, Cassia; Fiorini, Emma; Babolin, Chiara; Vukicevic, Marija; Morici, Catherine; Madani, Rime; Eligert, Valerie; Kosco-Vilbois, Marie; Roberts, Amanda; Becker, Ann; Pfeifer, Andrea; Mobley, William C. (Frontiers in Neuroscience, 2023)
Introduction People with DS are highly predisposed to Alzheimer’s disease (AD) and demonstrate very similar clinical and pathological features. Ts65Dn mice are widely used and serve as the best-characterized animal model of DS. Methods We undertook studies to characterize age-related changes for AD-relevant markers linked to Aβ, Tau, and phospho-Tau, axonal structure, inflammation, and behavior. Results We found age related changes in both Ts65Dn and 2N mice. Relative to 2N mice, Ts65Dn mice showed consistent increases in Aβ40, insoluble phospho-Tau, and neurofilament light protein. These changes were correlated with deficits in learning and memory. Discussion These data have implications for planning future experiments aimed at preventing disease-related phenotypes and biomarkers. Interventions should be planned to address specific manifestations using treatments and treatment durations adequate to engage targets to prevent the emergence of phenotypes.